Exploring livelihood strategies of herder households in Mongolia: income-based approach - gombodorj, ganchimeg (Applied Studies in Agribusiness and Commerce, 2021)
The classification of livelihood strategies is important for identifying different lifestyles and developing poverty reduction measures. The research was aimed to identify Mongolian herder households’ livelihood strategies and assess capital factors that impact their choice and livelihood outcomes in connection with wealth and poverty. A total of 350 herder households were surveyed using the stratified sampling methods from four different economic regions. The Income-Based Approach was applied to identify herder households’ livelihood strategies based on their primary income sources and Pearson correlation was used for assessing the influencing input. The study hypothesizes that herder households earn the majority of income sources from animal husbandry and an essential factor in the choice of livelihood strategy is the number of animals. The study found that livelihood strategies of nomadic herder households clustered into four main types: а) livestock income sources, solely b) earn from kinship and assistant herder salary in addition to livestock income; с) social benefits and pension income in addition to livestock income and d) income sources dependent on natural resources in addition to livestock income. Location, financial capital, and physical capital were the main factors for choosing a specific livelihood strategy. There was an insignificant difference between poor and wealthy herder households in terms of physical assets ownership. To reduce rural poverty, we need tailored sustainable development policies based on different herder households’ livelihood strategies. JEL code: Q01, Q12, I30, D19, D31